Myths and Accountants. - Bierman, Harold (The Accounting Review, 1965)
This article has a negative point of view about the current state of the accounting art. While taking this negative position, the writer must admit to having an overall point of view, which is on balance favorable to the current state of accounting practice favorable in the sense that progress has been made through the years and that useful data can be obtained from published financial information. Researchers generally know the basis of recording the information and researchers know that the certified public accountant has reduced the possibility of fraudulent information to a reasonable minimum. The state of the art could be much worse. Taking a more optimistic position, there have been changes in accounting thought and practice through the years and there will be additional changes in the future. Accounting is an inexact art, primarily concerned with measuring financial position and income. Accountants have to a great extent established confidence in the honesty of the information presented. The next step is to broaden the accountant's mandate and encourage him to exercise more leeway in deciding which economic events are susceptible of measurement. Even assuming that the present form of financial information is retained, supplementary statements prepared on different bases could be presented jointly with the conventional information.